Windows XP pocket reference - Karp, David A. (O'Reilly, 2003)
Windows XP Pocket Reference is a handy book for power users and system administrators who need a solid reference with quick answers, but not a lot of explanation. This book is a powerful tool that quickly covers XP's applications and tools, tasks and settings, and commands. Windows XP Pocket Reference covers the following topics:Getting StartedMouse and Keyboard ShortcutsComponents of Windows XPSetting LocatorRegistry TweaksCommand Prompt & Recovery ConsoleError MessagesPacked with information in an easy-to-read format, Windows XP Pocket Reference is perfect for someone familiar with Windows w.
"A compact guide to Windows XP"--Cover
Keywords: Microsoft Windows (Computer file); Operating systems (Computers); Microsoft Windows XP (Système d'exploitation); Systèmes d'exploitation (Ordinateurs); operating systems; COMPUTERS; Operating Systems; DOS; COMPUTERS; Operating Systems; Macintosh; COMPUTERS; Operating Systems; Windows Server & NT; COMPUTERS; Operating Systems; Windows Workstation; COMPUTERS; System Administration; Windows Administration